INTERNATIONAL EXPERIENCE IN LEGAL REGULATION OF HEALTH INSURANCE: A COMPARATIVE ANALYSIS - Boltaev Mansurjon Sotivoldievich (PT. Antis International Publisher, 2024)
Objective: This study aims to conduct a comprehensive comparative analysis of international health insurance systems, focusing on the legal regulation of health insurance to identify strengths and weaknesses. The goal is to develop evidence-based recommendations to improve Russia’s mandatory health insurance (MHI) system, addressing issues like funding, access to services, care quality, and legal frameworks. Method: The research applies a theoretical framework built on domestic and international scholarly works related to health insurance and insurance law. The study uses general scientific methods like analysis, synthesis, and comparison, complemented by comparative legal analysis and institutional review. Empirical data are drawn from legal acts, statistical data from organizations like WHO and ILO, and case studies. Results: The research identifies key health insurance models: state-funded (e.g., UK, Canada), social insurance (e.g., Germany, France), and private insurance (e.g., U.S.), each with distinct advantages and challenges. Global trends include an increasing role of the state in health insurance regulation and efforts to expand universal coverage. Countries are evolving from selective to universal health insurance systems, focusing on accessibility, affordability, and quality of care. Novelty: The study highlights the applicability of international models for enhancing Russia’s MHI system, focusing on expanding state regulation and ensuring universal coverage. Key recommendations include improving regulatory frameworks, addressing coverage gaps for specific groups like the self-employed and rural populations, and strengthening accountability among insurers and providers.